Ação do hormônio triodotironina (T3) altera a expressão gênica do oncogene Amphiregulin (Areg) el células tumorais de adenocarcinoma de mama - Sibio, Maria Teresa De [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The incidence of breast cancer (BC) has increased alarmingly in recent years. Several studies have been lead to the discovery of amphiregulin (AREG) as an oncogene, with its expression related to various cancer types. Our group showed the action of T3 on different genes in BC cells using microarray, but the mechanism which T3 regulates the expression of these genes and the involvement of ER have not been evaluated yet. The relationship between the expression of AREG and the presence of TH remains unknown, therefore, the aim of this study was to verify the nuclear and extra-nuclear action of T3 on AREG gene expression in breast adenocarcinoma cell lines, MCF-7 and MDA-MB-231. The cell lines were subjected to treatment with 10-8M T3 at the times 10', 30', 1h and 4h in the presence or the absence of Fulvestrant (ICI 182,780) - ER inhibitor, Actinomycin D (ACTD) - inhibitor of gene expression, cycloheximide (CHX) - inhibitor of protein synthesis, and LY294002 - inhibitor of PI3K pathway. The AREG mRNA levels were analyzed by RT-PCR. For data analysis we used ANOVA followed by the post hoc Tukey's test with a significance level of 5%. T3 increased AREG gene expression levels, compared to the control group in both cell lines, regardless of the incubation times. Our study confirms that AREG gene expression is increased in the presence of T3 in both cell lines and at all the times studied. The data from this study indicate that T3 might act through ER, decreasing AREG expression after 30' treatment in MCF-7 cells and did not alter the expression of this gene in MDA-MB-231 cells, which lack ER. Furthermore, we suggest that T3actionon AREG gene expression occurs indirectly. The T3 maintains AREG expression even after the inhibition of transcription. And, the PI3K pathway activation by T3 is required for the modulation of AREG in both cell lines studied

A incidência de câncer de mama (CM) tem aumentado de maneira alarmante nos últimos anos. Diversas pesquisas conduziram à descoberta de amphiregulin (AREG) como um oncogene, tendo sua expressão relacionada com diversos tipos de cânceres. Nosso grupo evidenciou a ação do T3 sobre diferentes genes em células de câncer de mama, por meio de microarray, porém nesse estudo não foi avaliado o mecanismo de ação pelo qual o T3 regula a expressão desses genes e o envolvimento de ER. A relação entre a expressão de AREG e a presença de HT permanece desconhecida, portanto, o objetivo do presente estudo foi verificar a ação nuclear e extra-nuclear do T3 na expressão gênica do oncogene AREG em linhagens celulares de adenocarcinoma de mama, MCF-7 e MDA-MB-231. As linhagens celulares foram submetidas ao tratamento com 10-8M de T3 nos tempos de 10', 30', 1h e 4h, na presença ou ausência de Fulvestrant (ICI 182,780), inibidor de ER, Actinomicina D (ACTD) - inibidor da expressão gênica, Ciclohexamida (CHX), inibidor da síntese protéica, e LY294002 - inibidor da via PI3K. O mRNA de AREG foi analisado pela técnica de RT-PCR. Para a análise dos dados foi utilizado ANOVA complementado com teste de Tukey e adotado significância mínima de 5%. O T3 elevou os níveis de expressão gênica de AREG, em relação ao grupo controle, nas duas linhagens celulares, independente dos tempos de incubação. Nosso trabalho confirma que a expressão gênica de AREG está aumentada na presença T3, em ambas as linhagens e em todos os tempos estudados. Os dados desse estudo indicam que T3 pode agir por meio de ER, diminuindo a expressão de AREG após 30' de tratamento nas células MCF-7 e não alterando a expressão desse gene nas células MDA-MB-231, as quais não possuem ER. Além disso, podemos sugerir que a ação de T3 sobre a expressão gênica de AREG ocorre de forma indireta. O T3 mantém a expressão de AREG mesmo após ...
Keywords: Mamas - Cancer; Hormonios tireoidianos; Triiodotironina; Expressão gênica; Adenocarcinoma; Thyroid hormones; Breast - Cancer